The Routledge companion to Victorian literature - Denisoff, Dennis, 1961-; Schaffer, Talia, 1968- (Routledge, 2020)
The Routledge Companion to Victorian Literature offers 45 chapters by leading international scholars working with the most dynamic and influential political, cultural, and theoretical issues addressing Victorian literature today. Scholars and students will find this collection both useful and inspiring. Rigorously engaged with current scholarship that is both historically sensitive and theoretically informed, the Routledge Companion places the genres of the novel, poetry, and drama and issues of gender, social class, and race in conversation with subjects like ecology, colonialism, the Gothic, digital humanities, sexualities, disability, material culture, and animal studies. This guide is aimed at scholars who want to know the most significant critical approaches in Victorian studies, often written by the very scholars who helped found those fields. It addresses major theoretical movements such as narrative theory, formalism, historicism, and economic theory, as well as Victorian models of subjects such as anthropology, cognitive science, and religion. With its lists of key works, rich cross-referencing, extensive bibliographies, and explications of scholarly trajectories, the book is a crucial resource for graduate students and advanced undergraduates, while offering invaluable support to more seasoned scholars.
Keywords: English literature -- 19th century -- History and criticism.; Littérature anglaise -- 19e siècle -- Histoire et critique.; LITERARY CRITICISM -- General.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; English literature; 1800-1899; handbooks.; Criticism, interpretation, etc.; Handbooks and manuals.; Guides et manuels.